Effects of Communication Impairments on Knowledge Acquisition - Odondo, Emily Ayieta (My University, 2014)
Knowledge acquisition is facilitated through communication and communication occurs through language. However, in individuals with communication impairments, effective communication is adversely tempered with. This implies that communication impairments would affect knowledge acquisition. The question, however, is how this happens? Little effort has been made to answer this question, as revealed by the literature. In the quest to establish the effects of communication impairments on knowledge acquisition, this paper adopts a descriptive design and critically analyzes how communication disorders affect knowledge acquisition. It does this by examining how different communication impairments interact with different strategies proposed for knowledge acquisition and the resultant outcome. The results show that communication impairments hinder knowledge acquisition. They create barriers that prevent efficient execution of the various strategies involved in acquiring knowledge. The paper then provides some practical suggestions on how to deal with the ensuing problem with the aim of promoting knowledge acquisition.
Keywords: Knowledge; Acquisition; Communication; Impairment; Language; Aphasia